1986
DOI: 10.7567/jjaps.25s1.55
|View full text |Cite
|
Sign up to set email alerts
|

Magnetophonon Resonance in InxGa1-xAs (x=0.53)

Abstract: Magnetophonon resonance effect of the transverse magnetoresistance is studied in In x Ga1-x As (x=0.53) using a magnetic field modulation technique at temperatures from 40 to 300 K. The resonance arises from GaAs-like phonons at higher temperatures and two mode resonance due to GaAs-like phonons and InAs-like phonons is observed at low temperatures. Band edge effective mass is determined to be 0.0409m 0 at 77 K and 0.0388m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Monte Carlo simulation here includes all the major scattering mechanisms except electron-electron scattering: acoustic, polar optical, intra-and inter-valley nonpolar optical phonon scattering, ionized impurity scattering and random alloy scattering. Experimentally it has been observed that InGaAs possesses both InAs-like LO phonons and GaAslike phonons [30,31]. However, Kobayashi et al [9] have observed that the existence of these two phonon modes has only a minor effect on charge transport and therefore they are neglected in this work.…”
Section: Scattering Rates In a Two-dimensional Electron Gasmentioning
confidence: 87%
“…The Monte Carlo simulation here includes all the major scattering mechanisms except electron-electron scattering: acoustic, polar optical, intra-and inter-valley nonpolar optical phonon scattering, ionized impurity scattering and random alloy scattering. Experimentally it has been observed that InGaAs possesses both InAs-like LO phonons and GaAslike phonons [30,31]. However, Kobayashi et al [9] have observed that the existence of these two phonon modes has only a minor effect on charge transport and therefore they are neglected in this work.…”
Section: Scattering Rates In a Two-dimensional Electron Gasmentioning
confidence: 87%